ANALISIS PELAKSANAAN ASESMEN NASIONAL BERBASIS KOMPUTER (ANBK) DI SEKOLAH DASAR - Zulhijrah; Shaleh; Sinta Bella; Muhammad Fadhlan Syahnaidi; Hasan, Moh Ferdi (Study program PGSD FKIP Universitas Bung Hatta, 2023)
Technology, Information and Communication (ICT), which is growing rapidly today, must be recognized as having an impact on all aspects of human life, including education, so that the implementation of the National Assessment using a computer-based system is called the Computer-Based National Assessment (ANBK). The research used a qualitative method with a case study approach, collecting data using observation, interviews and documentation. The results showed that SDN Puger has implemented a computer-based national assessment (ANBK), school readiness starts from preparation, implementation and implementation process. In the implementation, there are several obstacles faced, including the lack of infrastructure, inadequate network and lack of student understanding of ANBK question material. There are suggestions in overcoming these problems, namely teachers lending laptops for computer shortages at school, adding wifi at school so that the signal is stable when implementing ANBK and the school holds additional lessons outside of school hours that discuss AKM questions and the school also develops sapa litersi innovations (welcome morning literacy).